Settlement of Foreign Direct Investment (FDI) Disputes through Arbitration - AL-MUSLEHI, SALEM; AL HUMAIDI, THABIT (Journal of Ecohumanism, 2025)
This research delves into the complexities surrounding the settlement of Foreign Direct Investment (FDI) disputes through arbitration, addressing the lack of a uniform definition of investment, the role of arbitration in attracting and safeguarding foreign investments, and the implications of the Oman Commercial Arbitration Canter (OCAC). Through legal analysis and comparative assessments, the study aims to highlight the importance of arbitration in resolving FDI disputes, examining the criteria for defining investments, the impact on investors and host countries, and suggesting enhancements to the Omani Arbitration Law to bolster investor protection and streamline dispute resolution processes within Oman.